¿Qué educación, para qué cuerpos y qué sensibilidades? Una agenda de investigación - Galak, Eduardo (Ágora, 2022)
This book brings together a set of writings that thematize the education of the body and its sensitivities in various contexts of action and from different perspectives of analysis. Likewise, it includes a series of multiple discussions promoted from the perspective of pedagogy, didactics, history, sociology, anthropology, philosophy, among others, which were compiled in this work due to their relationship with the education-body framework.